2013
DOI: 10.3109/19401736.2013.766178
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the Korean bitterlingAcheilognathus koreensis(Cypriniformes; Cyprinidae)

Abstract: The complete mitochondrial genome was sequenced from the Korean bitterling Acheilognathus koreensis. The genome sequence was 16,563 bp in size, and the gene order and contents were identical with the same genera Acheilognathus signifier and other previously reported fish mitochondrial genomes. Of 13 protein-coding genes (PCGs), four genes (CO2, CO3, ND4, and Cytochrome b) had incomplete stop codons. The base composition of A. koreensis showed anti-G bias (13.69%) on the third position of PCGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…All GC skews in the 13 PCGs ranged from ‒ 0.428 to ‒ 0.179 except for nad6 (0.423). This result suggests that more C nucleotides are present in most PCGs, and nad6 only presented negative AT and positive GC skews, which is consistent with most previous reports of strand asymmetry in freshwater fish (Hwang et al 2013b , c ).…”
Section: Resultssupporting
confidence: 91%
“…All GC skews in the 13 PCGs ranged from ‒ 0.428 to ‒ 0.179 except for nad6 (0.423). This result suggests that more C nucleotides are present in most PCGs, and nad6 only presented negative AT and positive GC skews, which is consistent with most previous reports of strand asymmetry in freshwater fish (Hwang et al 2013b , c ).…”
Section: Resultssupporting
confidence: 91%
“…Kumgang fat minnow and the Korean oily bitterling belong to the order Cypriniformes, family Cyprinidae, mainly inhabit the upper reaches of the Han River and distribute in the rivers flowing into the South Sea or the West Sea toward the south of Geumgang. (Lee et al, 2008;Hwang et al, 2013). In this study, we isolated three novel strains (D17 T , D13, and D25 T ) during investigations of the gut mi-crobiota of the three fish using culture-dependent methods.…”
Section: Introductionmentioning
confidence: 93%
“…The laterally flattened spindle-shaped body of the oily bitterling is dark-brown on the dorsal side and light-brown on the ventral side. As part of a recent species preservation effort, genetic studies of Korean oily bitterling have been initiated; Hwang et al reported the complete mitochondrial genome sequence of A. koreensis [16]. Herein, we report the molecular cloning and characterization of the mlc2f gene of Korean oily bitterling ( Akmlc2f ) at the genomic DNA and mRNA levels.…”
Section: Introductionmentioning
confidence: 99%